"Chinese Harmony" and Contemporary Non-Tonal Music Theory - Rahn, Jay (Canadian University Music Review / Revue de musique des universités canadiennes, 1999)
Twentieth-century Chinese theorists and composers have developed a distinctively indigenous approach to harmony, based in part on earlier pentatonic traditions. Mixed as it is with conventions of diatonic and chromatic harmony imported from Europe and North America, the resulting "Chinese harmony" poses music-theoretical problems of coordinating diatonic and pentatonic scales, and tertial and quartal chords. A survey of Chinese harmony as expounded by Kang Ou shows these difficulties to be theoretically intractable within solely Chinese or Euro-American frameworks, but soluble through recent formulations in atonal—or more appropriately, non-tonal-theory, as advanced by such writers as John Clough.